2009
DOI: 10.1038/jid.2009.173
|View full text |Cite
|
Sign up to set email alerts
|

Global Gene Expression Analysis Reveals Evidence for Decreased Lipid Biosynthesis and Increased Innate Immunity in Uninvolved Psoriatic Skin

Abstract: Psoriasis is a genetically determined inflammatory skin disease. Although the transition from uninvolved into lesional skin is accompanied by changes in the expression of multiple genes, much less is known about the difference between uninvolved skin from psoriatic patients as opposed to skin from normal individuals. Multiple biochemical and morphological changes were reported decades ago in uninvolved psoriatic skin but remain poorly understood. Here we demonstrate dysregulation of 223 transcripts representin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
164
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(182 citation statements)
references
References 51 publications
15
164
3
Order By: Relevance
“…Characterization of altered gene expression patterns has provided insights into the pathophysiology of each disorder (9). In this study, we demonstrated up-regulation of Sprr2d, Defb3, Cdsn, and S100a9 expression in K14cre;Dlx3 Kin/f skin, indicating overlap in gene expression between this mouse model and the PS gene expression signature (9,22). Moreover, marked down-regulation of Dlx3 expression was detected in human psoriatic lesions, suggesting that the lack of Dlx3 transcriptional function is potentially involved in the pathophysiology of human inflammatory diseases.…”
Section: Discussionmentioning
confidence: 79%
“…Characterization of altered gene expression patterns has provided insights into the pathophysiology of each disorder (9). In this study, we demonstrated up-regulation of Sprr2d, Defb3, Cdsn, and S100a9 expression in K14cre;Dlx3 Kin/f skin, indicating overlap in gene expression between this mouse model and the PS gene expression signature (9,22). Moreover, marked down-regulation of Dlx3 expression was detected in human psoriatic lesions, suggesting that the lack of Dlx3 transcriptional function is potentially involved in the pathophysiology of human inflammatory diseases.…”
Section: Discussionmentioning
confidence: 79%
“…Computational analysis is essential in analyzing the extensive data retrieved from these studies by incorporating the integration of various 'omics' platforms to fully represent the underlying mechanism of psoriasis. Gudjonsson et al (2009) characterized and compared gene expression in skin from psoriatic patients to identify patterns that are involved in lipid metabolism, innate immunity, and keratinocyte differentiation. Coda et al (2012) investigated differential gene expression in samples of lesional and nonlesional skin to identify psoriatic disease-associated pathways at the tissue level.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the gene expression pattern of lesional psoriatic skin is significantly different from normal skin of unaffected individuals [117,134,140]. Additionally, the transition from non-involved into involved psoriatic skin is accompanied by changes in the expression of multiple genes [139]. Some of the earliest identified genes as having significant over-expression in involved psoriatic skin include transforming growth factor-α (TGF-α) [141], tumor necrosis factor-α (TNF-α) [142], vascular endothelial growth factor (VEGF) and its receptors [143] and proteinase inhibitors such as peptidase inhibitor 3 (SKALP) [144].…”
Section: Psoriasismentioning
confidence: 99%
“…Some of the earliest identified genes as having significant over-expression in involved psoriatic skin include transforming growth factor-α (TGF-α) [141], tumor necrosis factor-α (TNF-α) [142], vascular endothelial growth factor (VEGF) and its receptors [143] and proteinase inhibitors such as peptidase inhibitor 3 (SKALP) [144]. Whereas previous investigations have focused only on the expression of small number of genes [145], recently more comprehensive analyses such as have identified a wide range of dysregulated genes in lesional and non-lesional psoriatic skin samples compared with normal skin samples using microarray analyses [136,139,140].…”
Section: Psoriasismentioning
confidence: 99%
See 1 more Smart Citation